A distribuição de valor nas culturas de café, milho e soja: mensurando a participação do Estado - Francisco, Alexandre Pedroza (2018)
The degree of economic development of a country or region is demonstrated by the development of economic sectors that are divided according to the type of products, resources used or services provided. In this division of sectors, the value added by each economic sector induces the argument about the behavior of the distribution of wealth generated among the stakeholders. Since the 2000s, Brazilian society has been asking about the real nature of economic development in recent decades, seeking answers about which sector has the greatest capacity to add value. With regard to Brazil, the primary sector has a significant participation in the GDP and, for such research, it was sought to verify studies that evidenced the destination of value for the agents involved. Regarding the State agent, for the cultures shown, no recent studies have been found and the tax matter has never been so evident. As an example, in Brazil, the tax burden has grown significantly in recent years, currently reaching about 36% of the Gross Domestic Product (GDP). At the international level, there is a constant discussion about the balance between direct and indirect taxes. This brief scenario gives a good idea of the importance and relevance of the tax issue, in its most diverse dimensions and aspects. Therefore, the present study analyzed the distribution of the accounting value generated in the soy, maize and coffee crops to the State stakeholder, measuring in percentage the tax participation during the years 2008 to 2017 if using the Wagner Law from the Public Finance Theory. For the measurement of billing, the works of CONAB and CEPEA / ESALQ were used to measure tax collection, an investigation was made in the federal and state tax regulations and in the labor rights to measure the rates of incidence bases: a) Payroll; b) Income; c) Goods / Services and; d) Other Taxes that, according to CETAD represent 94.22% of the total taxes collected by the State in its last publication. As a result of the survey, due to the low disclosure of information about the number of producing establishments, and of the average number of hectares per establishment and per region, it was not possible to measure the state participation in the PF modality, being possible only in the PJ. However, it was not possible to conclude that the tax cost, in rate / percentage, for the establishment within the PJ is lower than in the PF, since the progressive income tax table and that the State participation in the capture of the value generated in the crops of the first sector is lower than expected, given that the State's share of the analyzed crops was 17.84% for soybean, 15.28% for coffee and 12.86% for corn in relation to the estimated revenue.